TUHAN DALAM FILSAFAT DIALOG MARTIN BUBER - Hilal, Muhammad (JURNAL PUSAKA : Media Kajian dan Pemikiran Islam, 2014)
Martin Buber is one of those prominent philosophers who offer alternatives to the problem of the distanced or separated view of objects. This view has rooted in the Eastern world, thanks to the Cartesian modern philosophy and the increasingly development of science.The Philosophy of Dialogue is Buberâ€™s proposal to overcome the problem of subject-object distancedness and separatedness. The Philosophy of Dialogue argues that reality is â€œrelationâ€. There are two kind of relations, according to Buber: I-Thou and I-It relation. The I-Thou relation is human experience as a totality; an original, spontaneous, unpretended and uninterested one that gives effect to the subject and the object as such. The I-It relation, on the contrary, is a distanced and power-pretended relation. It is the later relation that dominates philosophy and science in nineteenth century.Human has a central and fundamental place in Buberâ€™s metaphysical concept of â€œrelationâ€ because the whole beings exist in humanâ€™s encounter toward them. Buberâ€™s view about human nature, therefore, is the most basic of his entire philosophical thought.This philosophical standpoint enables Buber to begin his formulation on philosophy of religion. Buber expresses God as The Eternal Thou. With this expression, The Eternal Thou, Buber wants to move beyond all manifestations of humanâ€™s belief of God because it is not the understanding about God that Buber is pointing at, but the dialogical moment between man and God. Buber also argues that the only way to express the encounter with The Eternal Thou is by using paradoxical language. Only this paradoxical language can touch the most sublime side of that encounter.Keywords: Martin Buber, Filsafat Dialog, Relasi I-Thou dan I-It, The Eternal Thou, Bahasa Paradox